2005
DOI: 10.1007/s11010-005-8217-0
|View full text |Cite
|
Sign up to set email alerts
|

Human lung cell growth is not stimulated by lead ions after lead chromate-induced genotoxicity

Abstract: Chromate compounds are known human lung carcinogens. Water solubility is an important factor in the carcinogenicity of these compounds with the most potent carcinogenic compounds being water-insoluble or 'particulate'. Previously we have shown that particulate chromates dissolve extracellularly releasing chromium (Cr) and lead (Pb) ions and only the Cr ions induce genotoxicity. Pb ions have been considered to have epigenetic effects and it is thought that these may enhance the carcinogenic activity of lead chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…But, it does raise a question about the possible role of lead in the toxicity of the compound. Our previous studies in human cells demonstrated that lead does not contribute to the cytotoxic and genotoxic effects of lead chromate because it is poorly absorbed by cells (Wise, S. et al, 2004; 2005). We did check sea turtle cells and found very low lead uptake after lead chromate exposure (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, it does raise a question about the possible role of lead in the toxicity of the compound. Our previous studies in human cells demonstrated that lead does not contribute to the cytotoxic and genotoxic effects of lead chromate because it is poorly absorbed by cells (Wise, S. et al, 2004; 2005). We did check sea turtle cells and found very low lead uptake after lead chromate exposure (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Lead chromate (CAS# 7758-97-6, ACS reagent minimum 98% purity), a particulate Cr(VI) compound was administered as a suspension in water as previously described (Wise J et al, 2002). Lead chromate does not fully dissolve in tissue culture while sodium chromate does (Holmes et al, 2005; Wise S. et al, 2005). Thus, direct comparisons of the two chemicals using a common unit of measure is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…It is established that lead chromate partially dissolves outside the cell, releasing Pb and Cr ions that then enter the cell (9). Once inside the cell, the Cr ions induce the cytotoxic, growth-inhibiting, and genotoxic effects observed after exposure to lead chromate and the lead ions have no apparent effect (14,15,17,18). Thus far, the potential effects of Cr ions on centrosome amplification have not been studied, but a 30-hour exposure to soluble chromate induced aneuploidy, which suggests that Cr ions could have the capacity to cause centrosome amplification, although that study did not consider it (31).…”
Section: Discussionmentioning
confidence: 99%
“…The internalized Cr ions induce chromosome aberrations, DNA adducts, and DNA double-strand breaks (10)(11)(12)(13)(14)(15), whereas the internalized Pb ions are generally nongenotoxic (8,16). Two studies investigating potential epigenetic effects of Pb in lead chromate-induced carcinogenesis also show that Pb does not interfere with Crinduced cell death (17) or cause mitotic stimulation of Cr-damaged cells (18). In addition, internalized particles seem to have no toxic effect except for possibly a small contribution to cytotoxicity (17).…”
Section: Introductionmentioning
confidence: 99%
“…Chromium is a recognized carcinogen of the respiratory tract, lungs, and gastric mucosa epithelium [50][51][52][53][54][55][56]. Higher levels of Cr were found in blood plasma of people suffering from lymphoproliferative diseases [57], as well as hexavalent Cr genotoxicity measured by the amount of chromosome aberrations [58,59] and the amount of single and/or double-strand DNA breakage in human lymphocytes in vitro [60,61] and animal cells [62,63].…”
Section: Correlation Coefficients Between Elements In Rainwater Andmentioning
confidence: 99%